2018
DOI: 10.1007/s12291-018-0797-z
|View full text |Cite
|
Sign up to set email alerts
|

Blood Lead Levels in Occupationally Exposed Workers Involved in Battery Factories of Delhi-NCR Region: Effect on Vitamin D and Calcium Metabolism

Abstract: Workers involved in battery manufacturing or recycling factories are occupationally exposed to high concentrations of lead. In humans, lead can cause a wide range of biological effects depending upon the level and duration of exposure. The purpose of this study was to find out the blood lead levels (BLL) in occupationally exposed workers involved in battery industry in Delhi NCR region and to study whether lead affected the vitamin D (vit D) and calcium metabolism. For this study 100 occupationally lead-expose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
22
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 22 publications
4
22
0
1
Order By: Relevance
“… State/ union territories Case/million Death/million Total no. of healthy subjects Mean 25(OH)D levels (ng/ml) References Andhra Pradesh 5530 50 1936 18 [32] , [33] , [34] , [35] , [36] Assam 2390 6 768 26 [37] , [38] , [39] Bihar 940 4 50 30 [40] Chandigarh 1830 27 878 34 [41] , [42] , [43] , [44] , [45] , [46] Delhi 8970 249 2919 15 [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] , [65] , [66] , [67] , [68] Goa 7520 64 …”
Section: Resultsmentioning
confidence: 99%
“… State/ union territories Case/million Death/million Total no. of healthy subjects Mean 25(OH)D levels (ng/ml) References Andhra Pradesh 5530 50 1936 18 [32] , [33] , [34] , [35] , [36] Assam 2390 6 768 26 [37] , [38] , [39] Bihar 940 4 50 30 [40] Chandigarh 1830 27 878 34 [41] , [42] , [43] , [44] , [45] , [46] Delhi 8970 249 2919 15 [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] , [65] , [66] , [67] , [68] Goa 7520 64 …”
Section: Resultsmentioning
confidence: 99%
“…Very few studies reported the occupational exposure of lead in the workers in India. Recently, Himani et al [26] demonstrated effect of higher BLL on Vit D and calcium status in battery workers of Delhi-NCR region. Singamsetty et al [27] reported incidence of higher BLL (25.26 ± 2.121 lg/dl) in battery workers of Andhra Pradesh.…”
Section: Discussionmentioning
confidence: 99%
“…One reason might be that the measurement of smoking and drinking was not precise enough, which was limited by the design of our study, evaluating these factors by questionnaire. Another possible reason was that both lead and alcohol deplete vitamin B12 and folate in serum, which may concomitantly affect the ALAD activity [ 7 ]. In addition, increasing oxidative stress from lead exposure and smoking may also affect ALAD enzyme activity via the prooxidant–antioxidant disequilibrium [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…ALAD inhibition results in a buildup of aminolevulinic acid detectable in the plasma and urine. At the molecular level, lead displaces a zinc ion at the metal binding site, not the active site, producing inhibition through a change in the quaternary structure of the enzyme [ 5 , 6 , 7 ]. Thus, ALAD activity may be negatively related to higher blood lead levels.…”
Section: Introductionmentioning
confidence: 99%